Effect of variation of amount of extracting solutions on total flavonoid currency of ethanol extract of kelor leaves (Moringa oleifera L.) - Sugihartini Nining; Kusuma Putri Anindita; Kusbandari Aprilia; Hanifah Dini (BIO Web of Conferences)
Flavonoids in Moringa oleifera leaves have the potential as antioxidants and are utilized in various health products. So information is needed about optimizing the right solvent ratio during the extraction process to obtain effective and optimal results. This study was conducted to determine the effect of ethanol solvent ratio on total flavonoid content and yield. The ratio used was 1:10, 1:20, 1:40, and 1:60. Preparation of Moringa oleifera leaves ethanol extract using maceration method with 50% ethanol solvent. Extract standardization test includes organoleptic test and drying shrinkage test. The amount of yield was statistically analyzed using Linear Regression using the SPSS application. Determination of total flavonoid content using UV-Vis spectrophotometer instrument with AlCl3 reagent. Total flavonoid levels obtained were then statistically analyzed using the SPSS application One Way Anova method. Based on the results of the standardization test, Moringa oleifera leaves ethanol extract has met the test requirements. The yield of Moringa oleifera leaves ethanol extract from 1:10, 1:20, 1:40, and 1:60 ratios were 29.17%; 30.97%; 33.15%; and 37.15%, respectively. The optimal point of total flavonoid content was reached at a ratio of 1:20. The addition of more solvent than 1:20 ratio is no longer effective in increasing the total flavonoid content. The results of this study can then be used as a reference in the formulation of Moringa oleifera leaves extract cream and lotion.